If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -108 = -4(-5b + -3) Reorder the terms: -108 = -4(-3 + -5b) -108 = (-3 * -4 + -5b * -4) -108 = (12 + 20b) Solving -108 = 12 + 20b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-20b' to each side of the equation. -108 + -20b = 12 + 20b + -20b Combine like terms: 20b + -20b = 0 -108 + -20b = 12 + 0 -108 + -20b = 12 Add '108' to each side of the equation. -108 + 108 + -20b = 12 + 108 Combine like terms: -108 + 108 = 0 0 + -20b = 12 + 108 -20b = 12 + 108 Combine like terms: 12 + 108 = 120 -20b = 120 Divide each side by '-20'. b = -6 Simplifying b = -6
| xcubo+ycubo=35 | | P^4q^6/p^2q^3 | | 2x^3/2*x^1/7 | | (15a4-9a)/3a | | 4-2x=8+0.5x | | (3+ab)(7-ab)= | | (3+v)(5v-6)=0 | | X+6=6x+31 | | 2+5e=12 | | xcosy=ycosx | | -7=1+n | | y=2/3x-19 | | 10(x-9)-9(5-6x)=2(4x-1)+5(1-2x) | | 4|=/2x-1/=12 | | 16÷8/9 | | (5y+3)(4-y)=0 | | 4c-7=3c-7 | | X+23=5x+31 | | 3+11x=5x+9 | | Ln(14)=ln(x) | | -3x+9=-2(3x+3) | | 18x+33=18x+11 | | 15x-30=15x-30 | | .8x+8+.6x=57 | | F(x)=8-ln(9x) | | A=.5(18)(2) | | 5x+13=3x+33+70 | | 8j-8=64 | | 5x+13=3x+33 | | 30+y=-4 | | 5x+13=3+33 | | u^2-2u-20=0 |